Integrating and Processing Events from Heterogeneous Data Sources - Koga, Ivo; Medeiros, Claudia Bauzer (Anais do Brazilian e-Science Workshop (BreSci), 2012)
Environmental monitoring studies present many challenges. A huge amount of data are provided in different formats from different sources (e.g. sensor networks and databases). This paper presents a framework we have developed to overcome some of these problems, based on combining aspects of Enterprise Service Bus (ESB) architectures and Event Processing mechanisms. First, we treat integration using ESB and then use event processing to transform, filter and detect event patterns, where all data arriving at a given point are treated uniformly as event streams. A case study concerning data streams of meteorological stations is provided to show the feasibility of this solution.